Disorders of bone and mineral metabolism after renal transplantation - Massari, Pablo U. (1997)
A 27-year-old transplant patient was admitted to the Hospital PrivadoCentro Medico de COrdoba for a core decompression procedure on both femoral heads and a bone biopsy of the iliac crest. He had received a cadaveric graft 18 months prior to this admission after receiving chronic hemodialysis for 14 months. His renal failure was due to chronic glonierulonephritis of undefined cause. At the time of transplantation, his intact PTH serum level was 132 pg/dl and the serum aluminum concentration was 139.6 g/liter (Table 1). He was given immunosuppression therapy of steroids and cyclosporine. Diuresis began on the seventh postoperative day after a period of presumed acute tubular necrosis. Acute rejection (Banif I/lI on the biopsy specimen) occurred on postoperative day 12, and he was given a series of intravenous boluses of methylprednisolonc (250 mg twice daily for 3 days). The rejection resolved and he was discharged from the hospital on postoperative day 20; his serum creatinine was 2.2 mgldl.